2016
DOI: 10.3389/fmicb.2016.01784
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for Formation of Archaean Stromatolites before the Advent of Oxygenic Photosynthesis

Abstract: Stromatolites are solid, laminar structures of biological origin. Living examples are sparsely distributed and formed by cyanobacteria, which are oxygenic phototrophs. However, stromatolites were abundant between 3.4 and 2.4 Gyr, prior to the advent of cyanobacteria and oxygenic photosynthesis. Here I propose that many Archaean stromatolites were seeded at points of efflux of hydrogen sulfide from hydrothermal fields into shallow water, while their laminar composition arose from alternating modes of strictly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…( 2009 ) proposed an important role for cyanobacterial photothiotrophy, but long after the GOE. Recalling that all modern phyla harboring chlorophotoautotrophs have members that oxidize sulfide (Table 1 ), and that Allen ( 2016 ) recently proposed an origin of Archean stromatolites involving the growth of protocyanobacteria that oxidized H 2 S at RC1—a suggestion that is fully compatible with our present considerations—our thoughts on the possible role of photothiotrophy in Earth's history, summarized in Fig. 5 , are as follows.…”
Section: Photothiotrophy: Underestimated In Earth Historysupporting
confidence: 75%
See 1 more Smart Citation
“…( 2009 ) proposed an important role for cyanobacterial photothiotrophy, but long after the GOE. Recalling that all modern phyla harboring chlorophotoautotrophs have members that oxidize sulfide (Table 1 ), and that Allen ( 2016 ) recently proposed an origin of Archean stromatolites involving the growth of protocyanobacteria that oxidized H 2 S at RC1—a suggestion that is fully compatible with our present considerations—our thoughts on the possible role of photothiotrophy in Earth's history, summarized in Fig. 5 , are as follows.…”
Section: Photothiotrophy: Underestimated In Earth Historysupporting
confidence: 75%
“… 2015 ; Fischer, Hemp and Johnson 2016 ) but devote little attention to the role of H 2 S as an electron donor in the evolution of photosynthesis. Like Allen ( 2005 , 2016 ), we see an important role for photothiotrophy in the evolution of photosynthesis and in Earth's history.…”
Section: Photothiotrophy: Underestimated In Earth Historymentioning
confidence: 94%
“…Under these conditions, the biomechanical and chemical effects of ectomycorrhizal fungi on apatite weathering seemed to be minor, but these effects are probably dependent on the nutrient status of the forest. Enhanced colonisation of apatite by ectomycorrhizal hyphae in laboratory systems (Rosling et al, 2004;Smits et al, 2012) is also commonly found under field conditions, but only when P availability is low (Rosenstock et al, 2016;Bahr et al, 2015;Almeida et al, 2019). The potential for weathering by ectomycorrhizal fungi is probably much higher under these conditions and the nutrient status of the forest should be considered when biological weathering rates are quantified, at least for apatite weathering, where P status has a strong effect on fungal colonisation of apatite.…”
Section: Discussionmentioning
confidence: 93%
“…The sub-aerial biofilms that exist at this interface today remain stressful environments 10 (Gorbushina, 2007) but ionizing radiation levels are now much lower due to the thickening of the Earth's atmosphere, thought to be caused by the increase of the magnetic field dipole intensity due to the solidification of the inner core, caused by the cooling of the Earth (Doglioni et al, 2016). Biomarker evidence (Brocks et al, 1999) in rocks that formed 200 million years (Ma) before the increase in atmospheric oxygen suggests that oxygen was already being produced before 2.5 Ga. Oxygenic photosynthesis by cyanobacteria is a likely source of this oxygen but there is evidence that stromatolites were abundant 15 between 3.4 and 2.4 Ga, prior to the advent of cyanobacteria and oxygenic photosynthesis (Allen, 2016) and that Archaean microbial mats of protocyanobacteria switched between photolithoautotrophic and photoorganoheterotrophic metabolism prior to the evolution of cyanobacteria with simultaneous constitutive expression of genes allowing both types of metabolism. It is also likely that phototrophy based on purple retinal pigments similar to the chromoprotein bacteriorhodopsin, discovered in halophilic Archaea, may have dominated prior to the development of photosynthesis (DasSarma and Schweiterman, 2018).…”
Section: Systemic Consequences Of Microorganism-mineral Interactions mentioning
confidence: 99%